AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING DESCRIPTIVE TEXT - Ismayanti, Eni; Kholiq, Abdul (Universitas Islam Lamongan, 2020)
This research aims to describe the students’ difficulties in writing descriptive text and to find out the causes of students’ difficulties in writing descriptive text. This research uses quantitative descriptive methods. The research subjects are X MIPA 6 students of SMAN 1 Sukodadi who had difficulties when writing descriptive text, the data of this research are the result of students’ worksheet and the students’ answer in interview. This research used documentation and interview to collect the data. Data reduction, data display and drawing conclusion was used to analyze the data. The result of this research shows that the students of X MIPA 6 have difficulty in writing descriptive text, the difficulties are difficulties in generic structure, difficulties in grammar, and difficulties in spelling. While the factors that cause the students’ difficulties in writing descriptive text are lack of proficiency in the text production skills, lack of knowledge relating to the subject contents of the script to be written, and lack of interest in learning English.